Validity of Inquiry-Based Learning Tools on Students' Scientific Argumentation Ability - Dewi Firdausi Nuzulah; Tjandra Kirana; Muslimin Ibrahim (IJORER : International Journal of Recent Educational Research, 2023)
Objective: This study aims to describe the validity of inquiry-based learning tools on students' scientific argumentation abilities. The validity of the developed device is viewed from the aspects of content, language, and presentation. This type of research is pre-experimental without a control group. Method: The method used is the 4D model (define, design, and development), which is modified and implemented in the Postgraduate Program in Science Education, State University of Surabaya. The data collection technique was carried out using the learning device validation method. The assessment instrument uses a device validation sheet. The tools developed include LIP, ST, SAS, and students' scientific argumentation ability tests. Three biology lecturers assessed the validity of this inquiry-based learning tool. Data analysis was conducted quantitatively, and the Aiken validity index and reliability were calculated. Results: The validation results obtained the validity index Aikens LIP 0.97, ST 0.93, SW 0.99, and scientific argumentation test 1.00 with high validity and reliability categories. Novelty: the researcher considers that not many previous studies have conducted research on the material of the Human Respiratory System, especially in class XI Science based on guided inquiry which includes five indicators of scientific argument, namely claims, ground used, warrants given, counterarguments generated and rebuttal offered. However, this research focuses on the validation analysis of inquiry-based learning tools on high school students' scientific argumentation abilities.